Mugger Crocodile Research at Ramatirtha : a Review - Dani, C. S.; Sagar, S. R.; Singh, L. A. K. (Indian Forester, 1991)
This paper reviews efforts towards rebuilding viable population of mugger crocodiles in major rivers inside Simllipal Tiger Reserve. Improving captive management of and providing juvenile mugger crocodiles for release elsewhere. Literature on the subject has been reviewed and results of research at Ramatiratha presented along with recommendations for the future.